1991
DOI: 10.1021/bi00236a025
|View full text |Cite
|
Sign up to set email alerts
|

Comparative 2D NMR studies of human insulin and despentapeptide insulin: sequential resonance assignment and implications for protein dynamics and receptor recognition

Abstract: The solution structure and dynamics of human insulin are investigated by 2D 1H NMR spectroscopy in reference to a previously analyzed analogue, des-pentapeptide(B26-B30) insulin (DPI; Hua, Q.X., & Weiss, M.A. (1990) Biochemistry 29, 10545-10555). This spectroscopic comparison is of interest since (i) the structure of the C-terminal region of the B-chain has not been determined in the monomeric state and (ii) the role of this region in binding to the insulin receptor has been the subject of long-standing specul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
115
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(131 citation statements)
references
References 39 publications
16
115
0
Order By: Relevance
“…When it is dissolved in 'H,O, all amide protons exchange rapidly with the solvent. Recently Hua et al [37] reported that slowly exchanging amide protons were observed for des-(B26 -B30)-insulin under conditions similar to ours. In our 2D experiments using fresh material in 'H20, which take about 12-24 h at 300 K, no cross-peaks corresponding to amide resonances were observed.…”
Section: Local Mobilitysupporting
confidence: 86%
“…When it is dissolved in 'H,O, all amide protons exchange rapidly with the solvent. Recently Hua et al [37] reported that slowly exchanging amide protons were observed for des-(B26 -B30)-insulin under conditions similar to ours. In our 2D experiments using fresh material in 'H20, which take about 12-24 h at 300 K, no cross-peaks corresponding to amide resonances were observed.…”
Section: Local Mobilitysupporting
confidence: 86%
“…Because the amide line widths of 3G-DKP-insulin are appropriate for a small globular protein, less extensive anti- Table V. phase cancellation is observed in DQF-COSY spectra (37) and more efficient total correlation spectroscopy transfer is achieved. Similar technical improvement in NMR quality was observed on deleting residues B26 -B30 in NMR studies of DPI (38,39). We suggest that the detached (A1-A5) or deleted (B26 -B30) elements are coupled to non-local motions in the core of insulin; in native insulin and DKP-insulin, the millisecond time scale of such motions leads to incomplete averaging of NMR chemical shifts ("conformational broadening"; Refs.…”
Section: Discussionsupporting
confidence: 65%
“…By conventional criteria of sensitivity and resolution, the quality of the variant spectra is superior to that of DKP-insulin or native insulin (1,39). This "improvement" (a seeming paradox in light of the partial fold of the analog and its very low activity) reflects a reduction in the extent of anomalous broadening otherwise characteristic of insulin and insulin analogs (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…Effects of Urea on Monomeric Insulin Fibrillation-Insulin exists as a monomer in 20% acetic acid (30,45,52). The near-UV CD spectra of insulin measured in the presence of 20% acetic acid and various urea concentrations are represented in Fig.…”
Section: Kinetics Of Fibrillation For Hexameric Insulin In the Presenmentioning
confidence: 99%